PENERAPAN ASUHAN KEPERAWATAN PADA PASIEN TN. H DENGAN GGK DALAM PEMENUHAN KEBUTUHAN CAIRAN DAN ELEKTROLIT - Rahmawati, Rahmawati -; Wahyuni, Sri (Poltekkes Kemenkes Makassar, 2018)
ABSTRACTÂ Chronic Kidney Failure (CRF) is still a big problem in the world. According to WHO the growth of patients with CRF in 2013 increased 50% from the previous year. Every year 200.000 people undergo hemodialysis. Indonesia is a country with high rates of CPR sufferers. Permafri survey results estimated 12.5% of the population or 25 million Indonesian population has decreased kidney function. Monitoring of fluids and electrolytes as well as the level of adherence to fluid and electrolyte restrictions determines the quality of life of the patient.This study aims to describe nursing care in patients Mr. H with GGK in the fulfillment of fluid and electrolyte needs in Hemodialisa Room RSUD Labuang Baji Makassar.This research uses descriptive method with case study approach. The instruments used were interview guides, observation sheets, checklist and patient documentation records. Data were analyzed using nursing process approach.The results showed an imbalance of intertisial and intravascular fluid volume characterized by lower extremity edema, positive edema pitting 4, thirst, dizziness, itching, weakness and CRT> 3 seconds, oliguri. The application of nursing care is focused on monitoring the goal, blood flow, hourly rate and hourly TTV, fluid and electrolyte status, fluid and electrolyte restrictions, efforts to increase venous return and increase Urea Reduction Ration (URR) as well as fluid status monitoring and signs of dehydration (skin turgor, mucous membrane, urine output, CRT examination), and helps control thirst. In addition, it involves the patient and family to monitor the intake of fluid and electrolyte output for 24 hours and provide discharge planning for the management of home care in preventing fluid overload, resulting in fluid and electrolyte balance.Research conclusions show that treatment of patients with GGK undergoing HD with monitoring of fluids and electrolytes at home, effectively decreasing the degree of edema and body weightKeywords : Chronic Kidney Failure, Liquids and Electrolytes, Hemodialysis, NursingÂ Care